Measurements of Balance: Comparison of the Timed "Up and Go" Test and Functional Reach Test with the Berg Balance Scale - Fritz, Holly; Bennie, Scott; Peterson, Saundra; Dizon, Allan; Bruner, Kathryn; Goodman, Bob (Journal of Physical Therapy Science, 2003)
Objective: To compare the Timed "Up and Go" and Functional Reach tests to the Berg Balance Scale for concurrent validity in a broad adult population. Design: A prospective study of individuals with balance deficits. Setting: Neurological rehabilitation, skilled nursing, and acute care facilities. Subjects: Twenty subjects: 12 females and eight males, aged 38 to 86 years (μ=68, SD=14.5). Intervention: The order in which the three tests were performed on each subject was randomized and the scores from the three tests were analyzed using correlation coefficients. Main Outcome Measures: Balance and correlations were based on scores from each of the three balance tests performed. Results: There was a significant correlation between the Berg Balance Scale and Timed "Up and Go" test (r=0.47, p=0.04) but no significant correlation between the Berg Balance Scale and the Functional Reach test (r=0.42, p=0.06). Pairing the Timed "Up and Go" and Functional Reach tests however, revealed a significant correlation (R=0.56, p=0.04). Conclusion: This study suggests that the Timed "Up and Go" test alone or a combination of the Timed "Up and Go" and Functional Reach tests can be used as a simple measure of balance comparable to the Berg Balance Scale.